An Investigation of Undergraduate Students Cyberloafing Behaviors: An Example of Faculty of Education, EMU - Umaru, Zubairu Yandayi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The study was designed to investigate cyberloafing behaviours among the undergraduate students of Faculty of Education, Eastern Mediterranean University (EMU). Also to explore the cyberloafing behavioural effects of students in accordance with their difference in gender, levels of education, age groups and the effects of their academic CGPA. The study was designed based on quantitative and survey research method. Cyberloafing scale was used for data collection tool and was applied in the Faculty of Education. The research consisted about 116 Fall semester 2019-2020 registered undergraduate students who procured admission in the Faculty of Education at EMU who willingly partook in the survey. Descriptive analysis techniques was used to analyse all data collected. Both demographic and all the cyberloafing items was analysed by the use of ANOVA, frequency, percentage, as well as T-test for analysing the data mentioned in this study in order to achieve the aim proposed. However, finding derived from this study based on the Internet skills, on cyberloafing behaviours of undergraduate students of Faculty of Education EMU, significant difference was found between internet usage skills when relate it with the cyberloafing behaviours. Also significant difference was found in terms of gender with that of male higher. But in terms of their CGPA, there was no significant difference. Keywords: Computer laboratory, Cyberloafing / Cyberslacking, Information and Communication Technology (ICT) and Internet

ÖZ: Bu araştırma Doğu Akdeniz Üniversitesi Eğitim Fakültesinde okumakta olan lisans öğrencilerinin siber aylaklık davranışlarını incelemektedir. Ayrıca bu araştırma siber aylaklık davranışının öğrencilerin cinsiyet, eğitim yılı, genel not ortalaması (CGPA) ve yaş grupları üzerindeki davranışsal etkiyi araştırmaktadır. Araştırma anket metoduna dayalı nicel bir çalışmadır. Araştırma sırasında Eğitim Fakültesi’nde siber aylaklık ölçeği kullanılmıştır. Araştırma 2019-2020 akademik yılının güz döneminde 116 lisans öğrencisi ile yapılmıştır. Toplanan veriyi analiz etmek için tanımlayıcı istatistik tekniği kullanılmıştır. Araştırmanın amacına ulaşılabilmesi için demografik verinin yanında tüm siber aylaklık verisi ANOVA, sıklık, yüzdelik ve T-test yöntemleri kullanılmıştır. DAÜ Eğitim Fakültesi lisans öğrencilerinden internet becerileri ve siber aylaklık üzerine toplanan veri doğrultusunda internet kullanım becerileri ile siber aylaklık karşılaştırıldığında önemli farklılık olduğu tespit edilmiştir. Ayrıca cinsiyete bağlı önemli farklılık tespit edilmiş ve erkek öğrencilerde daha yüksek olduğu tespit edilmiştir. Ancak, genel not ortalamasına (CGPA) bağlı olan herhangi bir farklılık tespit edilmemiştir. Anahtar Kelimeler: Bilgisayar Laboratuvarı, Siber Aylaklık, Bilgi ve İletişim Teknolojileri, İnternet
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2020. Supervisor: Assist. Prof. Dr.İldeniz Özverir.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education--Online Learning; Education - Computer network resources--E-Learning--Moodle--Learning Management System; Educational Technology--Educational Media--E-Learning; Teaching - Computer network resources; Computer laboratory; Cyberloafing / Cyberslacking; Information and Communication Technology (ICT) and Internet